Cardiovascular Morbidity in a Warming Climate: A Systematic Review of Vulnerability and Adaptation - Anggun Novia Indah Fitri; Dianna Ratnawati; Gabriel Loi (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2026)
Rising global temperatures and increasing frequency of extreme heat events have transformed thermal stress into a critical, systemic driver of cardiovascular and chronic disease burden worldwide. Despite growing recognition of heat-related health risks, substantial gaps remain regarding chronic sub-threshold exposure, morbidity outcomes, and the equity implications of adaptation strategies. This systematic review, conducted according to PRISMA 2020 guidelines, synthesizes contemporary epidemiological evidence from peer-reviewed studies published between 2020 and 2025 to characterize heat-health associations, identify vulnerability determinants, and evaluate policy implementation across diverse geographic and socioeconomic contexts. Following independent screening, quality appraisal, and data extraction, a structured narrative synthesis was performed due to significant methodological heterogeneity in exposure metrics and outcome definitions. The findings demonstrate a robust association between heat exposure and elevated risks of stroke, coronary heart disease, and accelerated progression of metabolic, respiratory, and mental health conditions, with chronic thermal stress emerging as an underrecognized contributor to long-term physiological deterioration. Vulnerability is highly stratified, disproportionately affecting older adults, women, outdoor workers, socioeconomically marginalized communities, and populations in low- and middle-income countries, particularly within urban heat island environments. Current adaptation measures exhibit limited behavioral uptake and insufficient equity-focused design. Addressing these disparities requires standardized exposure metrics, context-sensitive early warning systems, multisectoral policy integration, and targeted research on chronic thermal stress to build inclusive, climate-resilient health systems.